Emerging Areas of Science, Engineering, and Medicine for the Courts: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On February 24-25, 2021, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop titled Emerging Areas of Science, Engineering, and Medicine for the Courts. The workshop was organized to explore emerging issues in science, technology, and medicine that might be the basis of new chapters in a fourth edition of the Reference Manual on Scientific Evidence. The Reference Manual, a primary resource for federal judges on questions of science in litigation, is a joint publication of the National Academies of Sciences, Engineering, and Medicine and the Federal Judicial Center, the research and education arm of the federal judiciary. Over the course of the workshop, judges discussed how they evaluate scientific evidence in court and scientists and others spoke about emerging issues in science and technology that may come before the courts in coming years. This publication highlights the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences

The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Each year, tens of millions of individuals in the U.S. suffer from neurological and psychiatric disorders including neurodegenerative diseases such as Alzheimer's Disease and Parkinson's Disease, and psychiatric disorders such as autism spectrum disorder, depression and schizophrenia. Treatments for these diseases are often completely lacking or only partially effective, due in large part to the difficulty of conducting brain research and the complexity of the brain itself. Researchers in recent years have developed new models to better represent and study the human brain. The three models considered in this report, all of which generate and use pluripotent stem cells from healthy individuals and patients, are human neural organoids, human neural transplants, and human-animal neural chimeras. The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance reviews the status of research, considers its benefits and risks, discusses associated ethical issues, and considers governance mechanisms for this type of research.
Keywords: Health and Medicine

Science and Judgment in Risk Assessment - National Research Council (The National Academies Press, 1994)
The public depends on competent risk assessment from the federal government and the scientific community to grapple with the threat of pollution. When risk reports turn out to be overblown—or when risks are overlooked—public skepticism abounds. This comprehensive and readable book explores how the U.S. Environmental Protection Agency (EPA) can improve its risk assessment practices, with a focus on implementation of the 1990 Clean Air Act Amendments. With a wealth of detailed information, pertinent examples, and revealing analysis, the volume explores the "default option" and other basic concepts. It offers two views of EPA operations: The first examines how EPA currently assesses exposure to hazardous air pollutants, evaluates the toxicity of a substance, and characterizes the risk to the public. The second, more holistic, view explores how EPA can improve in several critical areas of risk assessment by focusing on cross-cutting themes and incorporating more scientific judgment. This comprehensive volume will be important to the EPA and other agencies, risk managers, environmental advocates, scientists, faculty, students, and concerned individuals.
Keywords: Environment and Environmental Studies

High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps: Proceedings of a Workshop-in Brief - Anne Johnson (The National Academies Press, 2023)
The U.S. Department of Defense faces a complex array of challenges in its efforts to retain a position of technological dominance and to protect national security. Several aspects of materials and manufacturing, especially the ability of materials to operate with predictable behaviors in high-temperature environments, pose particular challenges. To illuminate issues surrounding novel high-temperature materials discovery, development, manufacturing, and application, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps on May 10-11, 2022. This publication summarizes the presentations and discussion of the workshop.

Women's Adventures in Science Seven-Volume Set (The National Academies Press)
What would it be like to build the first robot that could interact with people? Or to study human remains in search of criminal evidence? In Women's Adventures in Science, readers will learn about the trailblazing women who are leaders in a variety of scientific fields, from robotics to forensics. Each book focuses on the life and work of a woman active in her field today, providing readers with insights into the personal and professional paths that led to their careers in science. The companion Web site, www.iwaswondering.org, offers another way to "meet" these inspiring women scientists. The fun, interactive site builds on the content of the books and includes games, comic strips, videos, activities, and a timeline of women in science. Three titles from the original Women's Adventures in Science series, Strong Force, Beyond Jupiter, and Forecast Earth, are no longer available.
Keywords: Biography and Autobiography

Legal Issues and Emerging Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The nation’s 6,800 plus public transportation agencies need to have access to a program that can provide authoritatively researched, specific studies of legal issues and problems having national significance and application to the public transportation industry. Some legal issues and problems are unique to transit agencies. The TRB Transit Cooperative Research Program's TCRP Legal Research Digest 59: Legal Issues and Emerging Technologies provides transportation attorneys with guidance and resources to assist with these legal changes resulting from the implementation of technology, including regulatory challenges, risk management, cybersecurity, privacy, handling confidential and proprietary information, intellectual property rights, civil rights and environmental justice compliance, labor and employment law, and procurement issues.
Keywords: Transportation and Infrastructure

The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard’s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.
Keywords: Transportation and Infrastructure

Emerging Safety Science: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
In recent years, the costs of new drug development have skyrocketed. The average cost of developing a new approved drug is now estimated to be $1.3 billion (DiMasi and Grabowski, 2007). At the same time, each year fewer new molecular entities (NMEs) are approved. DiMasi and Grabowski report that only 21.5 percent of the candidate drugs that enter phase I clinical testing actually make it to market. In 2007, just 17 novel drugs and 2 novel biologics were approved. In addition to the slowing rate of drug development and approval, recent years have seen a number of drugs withdrawn from the market for safety reasons. According to the Government Accountability Office (GAO), 10 drugs were withdrawn because of safety concerns between 2000 and March 2006 (GAO, 2006). Finding ways to select successful drug candidates earlier in development could save millions or even billions of dollars, reduce the costs of drugs on the market, and increase the number of new drugs with improved safety profiles that are available to patients. Emerging scientific knowledge and technologies hold the potential to enhance correct decision making for the advancement of candidate drugs. Identification of safety problems is a key reason that new drug development is stalled. Traditional methods for assessing a drug's safety prior to approval are limited in their ability to detect rare safety problems. Prior to receiving U.S. Food and Drug Administration (FDA) approval, a drug will have been tested in hundreds to thousands of patients. Generally, drugs cannot confidently be linked to safety problems until they have been tested in tens of thousands to hundreds of thousands of people. With current methods, it is unlikely that rare safety problems will be identified prior to approval. Emerging Safety Science: Workshop Summary summarizes the events and presentations of the workshop.
Keywords: Health and Medicine

Emerging Technologies and Innovation in Manufacturing Regenerative Medicine Therapies: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
As the number of regenerative medicines and therapies approved by the Food and Drug Administration (FDA) has grown to meet rising demand, the field of regenerative medicine has started to anticipate the potential of strategies such as artificial intelligence, decentralized manufacturing, and automation to accommodate this expansion. The National Academies Forum on Regenerative Medicine hosted a public workshop in October 2023 to explore emerging technologies, evolving manufacturing approaches, regulatory considerations, and diverse partnerships needed to increase regenerative medicine treatment capacity.
Keywords: Health and Medicine

Building Resilience in the Face of Emerging Threats to Child and Youth Well-Being: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of growing threats to child and youth well-being - whether it be the COVID-19 pandemic, climate change, systemic racism, or new crises that have yet to arise - it is imperative that youth well-being be promoted through the development of strong resilience skills. To explore strategies for building youth resilience, the National Academies of Sciences, Engineering, and Medicine Forum for Childrens Well-Being held a 3-day workshop in October 2022. The workshop included presentations from experts, as well as moderated conversations between the presenters and youth discussants. This Proceedings of a Workshop-in Brief provides a high-level summary of the topics addressed in the workshop.
Keywords: Behavioral and Social Sciences

Sustainable and Resilient Supply Chains Using Emerging Technologies: Policy Options: Proceedings of a Workshop–in Brief - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The coronavirus disease 2019 (COVID-19) crisis sparked concerns about the vulnerability of supply chains and the significant impact of their disruption on the economy and society within the U.S. and abroad. Issues around global supply chains existed before the pandemic but were also greatly aggravated by it. To consider these issues, the Science and Technology for Sustainability program, in collaboration with the Resilient America Program, Transportation Research Board, and Board on Atmospheric Sciences and Climate at the National Academies of Sciences, Engineering, and Medicine, held a series of four virtual workshops on February 3, 4, 17, and 18, 2021. The workshop series addressed opportunities, challenges and environmental implications of increasing local inclusion and community participation in global value chain networks by using new technologies to strengthen resilience and sustainability in the face of recurring disruptions. The series also explored the feasibility of introducing advanced manufacturing, logistics and decision-making under alternative supply chain scenarios in different sectors, with a view to strengthening the resilience of communities and adopting far more environmentally and economically sustainable consumption and production approaches. This publication summarizes the presentations and discussion of the workshops.
Keywords: Environment and Environmental Studies

Sex Differences in Brain Disorders: Emerging Transcriptomic Evidence: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Accumulating evidence gathered over the past three decades has demonstrated a biological basis for differences between men and women with respect to clinical features and treatment responses to several neuropsychiatric, neurodevelopmental, and neurodegenerative disorders. Dramatic sex differences have also been identified in the brain transcriptomes of individuals with multiple brain disorders, including depression, posttraumatic stress disorder, and autism. The brain transcriptome includes all of the messenger RNA as well as the non-protein-coding RNA molecules expressed in brain tissue and thus represents gene activity. To explore these sex-based transcriptomic differences further, the National Academies of Sciences, Engineering, and Medicine's Forum on Neuroscience and Nervous System Disorders hosted a workshop on September 23, 2020, titled Sex Differences in Brain Disorders: Emerging Transcriptomic Evidence and Implications for Therapeutic Development. The workshop brought together a broad spectrum of stakeholders to share cutting-edge emerging evidence, discuss challenges, and identify future opportunities and potential directions. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Improving the CDC Quarantine Station Network's Response to Emerging Threats - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Centers for Disease Control and Prevention (CDC) is responsible for preventing the introduction, transmission, and spread of communicable diseases into the United States. It does this primarily through the Division of Global Migration and Quarantine (DGMQ), which oversees the federal quarantine station network. Over the past two decades, the frequency and volume of microbial threats worldwide have continued to intensify. The COVID-19 pandemic, in particular, has prompted a reevaluation of many of our current disease control mechanisms, including the use and role of quarantine as a public health tool. The emergence of COVID-19 prompted CDC to request that the National Academies of Sciences, Engineering, and Medicine convene a committee to assess the role of DGMQ and the federal quarantine station network in mitigating the risk of onward communicable disease transmission in light of changes in the global environment, including large increases in international travel, threats posed by emerging infections, and the movement of animals and cargo. The committee was also tasked with identifying how lessons learned during COVID-19 and other public health emergencies can be leveraged to strengthen pandemic response. The report's findings and recommendations span five domains: organizational capacity, disease control and response efforts, new technologies and data systems, coordination and collaboration, and legal and regulatory authority.
Keywords: Health and Medicine

Next Generation Earth Systems Science at the National Science Foundation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Science Foundation (NSF) has played a key role over the past several decades in advancing understanding of Earth's systems by funding research on atmospheric, ocean, hydrologic, geologic, polar, ecosystem, social, and engineering-related processes. Today, however, those systems are being driven like never before by human technologies and activities. Our understanding has struggled to keep pace with the rapidity and magnitude of human-driven changes, their impacts on human and ecosystem sustainability and resilience, and the effectiveness of different pathways to address those challenges. Given the urgency of understanding human-driven changes, NSF will need to sustain and expand its efforts to achieve greater impact. The time is ripe to create a next-generation Earth systems science initiative that emphasizes research on complex interconnections and feedbacks between natural and social processes. This will require NSF to place an increased emphasis on research inspired by real-world problems while maintaining their strong legacy of curiosity driven research across many disciplines – as well as enhance the participation of social, engineering, and data scientists, and strengthen efforts to include diverse perspectives in research.
Keywords: Earth Sciences

Emerging Challenges to Priced Managed Lanes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
There is a wide disparity between the goals that state departments of transportation (DOTs) have for priced managed lanes and the public assumption for those goals. The public tends to be highly skeptical of priced managed lanes because the concept is difficult to explain to a nontechnical audience.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 559: Emerging Challenges to Priced Managed Lanes provides an overview of the state of the practice of how state DOTs address challenges to implementing tolling, or pricing, on their managed lane systems.The synthesis entailed an extensive literature review of 60 publications and over 700 online media articles, a survey distributed to all 50 state DOTs, and a sampling of six case examples that explained specific examples of how agencies addressed challenges.
Keywords: Transportation and Infrastructure

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation—but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.
Keywords: Health and Medicine

The Role of Science in Solving the Earth's Emerging Water Problems - National Academy of Sciences (The National Academies Press, 2005)
Earth is about 70% water, the human body is about 53% water, plants use water's unique properties to transport food, and aquatic organisms can survive during the winter due to water's thermal properties. However, as life continues to evolve on Earth, new problems with water emerge. The Sackler NAS Colloquium The Role of Science in Solving the Earth Emerging Water Problems provides a look into these problems ranging from water's agricultural use and importance in society to its scarcity and use in technology. (Sackler NAS Colloquium) The Role of Science in Solving the Earth Emerging Water Problems includes the colloquium, held October 8-14, 2004, program and abstracts of its presentations and posters. Also available in this book is the participant roster.
Keywords: Earth Sciences; Environment and Environmental Studies

Storms from the Sun: The Emerging Science of Space Weather - Michael J. Carlowicz; Ramon E. Lopez (The National Academies Press, 2002)
From the casual conversation starter to the 24-hour cable channels and Web sites devoted exclusively to the subject, everyone talks about weather. There's even weather in space and it's causing major upsets to our modern technological world. Space weather is all around us. There are no nightly news reports on space weather (yet), but we're rapidly developing the tools necessary to measure and observe trends in cosmic meteorology. New probes are going on-line that help us monitor the weather taking place miles above the Earth. But why does space weather matter? It doesn't affect whether we bring an umbrella to work or require us to monitor early school closings. It's far, far away and of little concern to us . . . right? March 13, 1989. The Department of Defense tracking system that keeps tabs on 8,000 objects orbiting Earth suddenly loses track of 1,300 of them. In New Jersey, a $10 million transformer is burned up by a surge of extra current in the power lines. Shocks to a power station in Quebec leave 6 million people without electricity. New England power stations struggle to keep their power grid up. Listeners tuning in to their local stations in Minnesota hear the broadcasts of the California Highway Patrol. Residents of Florida, Mexico, and the Grand Cayman Islands see glowing curtains of light in the sky. All of these bizarre, and seemingly unconnected, events were caused by a storm on the Sun and a fire in the sky. A series of solar flares and explosions had launched bolts of hot, electrified gas at the Earth and stirred up the second largest magnetic storm in recorded history. Before rockets and radio and the advent of other modern devices, we probably would never have noticed the effects of this space storm. But in today's electrically powered, space-faring world, the greatest space storm of the twenty-second solar maximum rang like a wake-up call. And we are now in the midst of another solar maximum, the effects of which are expected to be felt all the way through the year 2004. Storms from the Sun explores the emerging physical science of space weather and traces its increasing impact on a society that relies on space-based technologies. Authors Carlowicz and Lopez explain what space weather really means to us down here, and what it may mean for future explorations and colonization of distant worlds. By translating the findings of NASA and other top scientists into fascinating and accessible descriptions of the latest discoveries, we are privy to some of the most closely held secrets that the solar terrestrial system has to offer.
Keywords: Explore Science; Space and Aeronautics

Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats: Annual Report 2021 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The wide-ranging portfolio of the standing committee’s work has illuminated many aspects of the COVID-19 pandemic and response efforts. This Annual Report summarizes the committee’s work in 2021 and highlights the short consensus study reports, rapid expert consultations, and meetings conducted during the year.

Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats: Annual Report 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Since March 2020, the standing committee has consistently generated real-time policy recommendations and paved the way for the National Academies to produce an unprecedented amount of timely, evidence-based guidance in response to the COVID-19 pandemic. This Annual Report summarizes the committee’s work in 2020 and highlights the short consensus study reports, rapid expert consultations, meetings, and affiliated activities conducted during the year.